Causality between economic policy uncertainty and real housing returns in emerging economies: A cross-sample validation approach - Goodness C. Aye (Cogent Economics & Finance, 2018)
This paper examines whether economic policy uncertainty (EPU) causes real housing returns in 8 emerging economies for which EPU data are available namely: Brazil, Chile, China, India, Ireland, Russia, South Africa and South Korea. Quarterly data were used for the analysis. The study uses cross-sample validation (CSV) Granger causality approach which obviates the need to partition the data into an in-sample and out-of-sample periods when limited data are available as in this study. Results based on the CSV full sample period indicate no evidence of economic policy uncertainty Granger causing real housing returns except for Chile and China. However, based on CSV rolling window results, there is evidence of time varying causality in all the countries except India. The implications of these findings are drawn.
Keywords: C32; C53; G10; G17; 330; economic policy uncertainty; housing returns; cross-sample validation causality; in-sample; post-sample; rolling window